La produzione sociale di memorie marginali. I casi studio delle minoranze del Somaliland e dei giovani migranti somali in Italia - Elia Vitturini (Archivio Antropologico Mediterraneo)
The narration and sharing of the past represent a space in which social relations and cultural repertoires are reproduced. Somali groups distributed in the Horn of Africa and several diasporas have developed different types of social laboratories through which memories about the past of individuals and communities are elaborated and produced. Two case studies, explored through historical-ethnographic research in the Somali territories and Italy, show the historical dynamics of some of these laboratories that elaborate experiences of subordination, emancipation and marginality. The comparative analysis of the two examples reconstructs the factors of the trajectories that push some memories towards the margins of and disconnect from ongoing historical processes, from the social and cultural repertoire of Somali belonging. These are the oral memories cherished by some members of a minority and marginalized status group in present-day Somaliland, and the travel experiences of young migrants who, since 2010s, have arrived in Italy.